Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ajpath.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

H7N9 Influenza A Virus Exhibits Importin-α7–Mediated Replication in the Mammalian Respiratory Tract

Abstract: The acute respiratory distress syndrome (ARDS) is the leading cause of death in influenza A virus (IAV)-infected patients. Hereby, the cellular importin-α7 gene plays a major role. It promotes viral replication in the lung, thereby increasing the risk for the development of pneumonia complicated by ARDS. Herein, we analyzed whether the recently emerged H7N9 avian IAV has already adapted to human importin-α7 use, which is associated with high-level virus replication in the mammalian lung. Using a cell-based vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…7 ). Moreover, previous studies demonstrated that importin-α7 was crucial for enhanced viral replication and severe damage in mice using importin-α7 knockout mice 27 29 . Therefore, future studies will be required to investigate the molecular mechanism of the enhanced viral replication and pathogenicity mediated by the D701N mutation using the importin-α7 knockout mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Moreover, previous studies demonstrated that importin-α7 was crucial for enhanced viral replication and severe damage in mice using importin-α7 knockout mice 27 29 . Therefore, future studies will be required to investigate the molecular mechanism of the enhanced viral replication and pathogenicity mediated by the D701N mutation using the importin-α7 knockout mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, importin-α interacts to different NLSs on viral polymerase subunits to mediate the nuclear import of vRNP such as NLS at aa residues 449–495 and 738–755 of PB2 [ 202 ], NLS at aa residues 187–211 of PB1 [ 203 ] and NLS at aa residues 124–139, E154, 186–247 of PA [ 204 ]. Interestingly, 319K (NP), 701N (PB2), and 627K (PB2) are important to adapt the binding of vRNP from influenza virus of avian origin to mammalian importin-α7 isoform [ 205 , 206 , 207 , 208 ]. However, IAVs with the avian signatures (627E and 701D) depend primarily on importin-α3 [ 207 , 208 ].…”
Section: Viral Determinants For Zoonotic Potential Of Iavmentioning
confidence: 99%
“…Importin-α7 additionally promotes virus replication by a yet unknown mechanism beyond nuclear transport, supporting high-level IAV replication in various mammalian, including human cells (3). Most importantly, it could be shown that mice lacking the importin-α7 gene can no longer support high-titer virus replication of PB2 627K or 701N adapted influenza strains in the murine respiratory tract, leading to up to 100% survival upon influenza challenge (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%